The Influence of Work Motivation and Work Discipline on Employee Performance at the Photo Image and Watch Shop in Wonosobo - Wulan Mustika Rizqi; Eko Prasojo (Penerbit Hellow Pustaka, 2024)
This research aims to determine the influence of work motivation and work discipline on employee performance. The data analysis technique used in this research is multiple linear analysis, using the F test and t test. Collecting data using a questionnaire with a sample of 45 permanent employees, and the results of multiple linear regression, showed that work motivation variables had a significant effect on employee performance, research showed that the work motivation variable obtained a thitung value of 5.415 and a significance value of = 0.000, then obtained thitung > ttable or 5.415 > 2.018, and a significant value of 0.000 < 0.05, so Ha is accepted, which means that the work motivation variable (X1) partially has a significant effect on employee performance (Y). Work discipline has a significant effect on employee performance, research shows that the work discipline variable obtained a thitung value of 3,983 and a significance value of = 0.000, then obtained a thitung > ttable or 3,983 > 2,018, then Ha is accepted which means that the work discipline variable (X2) partially has a significant effect on employee performance (Y). And the results of the F test show that there is a significant influence between work motivation and work discipline on the performance of photo and watch image shop employees in Wonosobo, the test results obtained an F count value of 56,807, so it is said to be Fcount > Ftable or 56,807 > 3,219, and the significance value is 0.000 < 0.05, Ha is accepted, which means that the variables work motivation (X1) and work discipline (X2) simultaneously have a significant influence on employee performance (Y). The conclusion from the results of this research is that improving employee performance cannot be separated from work motivation and work discipline. With the high work motivation and work discipline they have, it will be easier to improve employee performance.